Junk Food Exposure Disrupts Selection of Food-Seeking Actions in Rats - Kosheleff, Alisa R.; Araki, Jingwen; Tsan, Linda; Chen, Grace; Murphy, Niall P.; Maidment, Nigel T.; Ostlund, Sean B. (Frontiers in Psychiatry, 2018)
There is growing evidence that repeated consumption of highly palatable, nutritionally poor ‘junk food’ diets can produce deficits in cognition and behavioral control. We explored whether long-term junk-food diet exposure disrupts rats’ ability to make adaptive choices about which foods to pursue based on 1) expected reward value (outcome devaluation test) and 2) cue-evoked reward expectations (Pavlovian-to-instrumental test). Rats were initially food restricted and trained on two distinct response-outcome contingencies (e.g., left press → chocolate pellets, and right press → sweetened condensed milk) and stimulus-outcome contingencies (e.g., white noise → chocolate pellets, and clicker → sweetened condensed milk). They were then given 6 weeks of unrestricted access to regular chow alone (controls) or chow and either 1 or 24 h access to junk food per day. Subsequent tests of decision making revealed that rats in both junk-food diet groups were impaired in selecting actions based on either expected food value or the presence of food-paired cues. These data demonstrate that chronic junk food consumption can disrupt the processes underlying adaptive control over food-seeking behavior. We suggest that the resulting dysregulation of food seeking may contribute to overeating and obesity.